2015
DOI: 10.4239/wjd.v6.i1.167
|View full text |Cite
|
Sign up to set email alerts
|

Rare complications of pediatric diabetic ketoacidosis

Abstract: The incidence of type 1 diabetes (T1D) among youth is steadily increasing across the world. Up to a third of pediatric patients with T1D present with diabetic ketoacidosis, a diagnosis that continues to be the leading cause of death in this population. Cerebral edema is the most common rare complication of diabetic ketoacidosis in children. Accordingly, treatment and outcome measures of cerebral edema are vastly researched and the pathophysiology is recently the subject of much debate. Nevertheless, cerebral e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
77
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(93 citation statements)
references
References 77 publications
1
77
0
6
Order By: Relevance
“…In the presence of hyperglycemia, an elevated or normal serum sodium concentrations indicate a clinically significant deficit in total body water (8). The report of one study suggested that high serum sodium and glucose levels represent the most important determinants for the occurrence of rhabdomyolysis (9), a known rare complication of DKA (4,10). In a study in USA involving children aged below 17 years with DKA, 33% of the patients had hypernatremia (11).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the presence of hyperglycemia, an elevated or normal serum sodium concentrations indicate a clinically significant deficit in total body water (8). The report of one study suggested that high serum sodium and glucose levels represent the most important determinants for the occurrence of rhabdomyolysis (9), a known rare complication of DKA (4,10). In a study in USA involving children aged below 17 years with DKA, 33% of the patients had hypernatremia (11).…”
Section: Introductionmentioning
confidence: 99%
“…Although it is estimated that a total body potassium deficit of 3-6mmol/kg occurs at presentation of DKA, pretreatment serum potassium levels are usually normal due to the intracellular shift of potassium that occurs with metabolic acidosis and insulin deficiency (10). In this regard, hypokalemia occurs only in 5-10% of patients at presentation of DKA but very rarely is the concentration less than 2.5mmol/L (12,13).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Diabetic ketoacidosis (DKA), characterized by hyperglycemia and acidosis, occurs in children with new onset of type 1 diabetes mellitus (T1DM) with a prevalence of approximately 30% . There are several complications of DKA described in children, including cerebral edema, stroke, pancreatitis, gastritis, pulmonary edema, and rhabdomyolysis . Acute kidney injury (AKI), with a rise in creatinine and uric acid, also occurs frequently in DKA and is likely due to severe dehydration .…”
Section: Introductionmentioning
confidence: 99%
“…Outcome of DKA was defined in terms of death or survival without considering any acute or chronic problems during the one year follow-up, e.g. cerebral edema and related consequences, renal failure, rhabdomyolysis, stroke, deep vein thrombosis (DVT), pneumomediastinum, acute respiratory distress syndrome (ARDS) with pulmonary edema, and gastrointestinal complications (11)(12)(13).…”
Section: Participants Data Acquisition and Variable Definitionmentioning
confidence: 99%